The life of Nelson - Southey, Robert, 1774-1843. (London)
1 online resource
Keywords: The Life of Nelson is one of Robert Southey's most influential and bestselling works. This new edition will contain a comprehensive critical apparatus that will make sense of the major issues posed by the text and how it contributes to studies of both Southey and Romanticism. The edition will feature a critical and contextual introduction, which will set out the origins and composition of the text together with its publication history, as well as offer a carefully considered view of the interplay between the Life and other biographies of Nelson, bringing into view the wide array of sources and influences Southey drew from.